2021
DOI: 10.1038/s41380-021-01035-y
|View full text |Cite
|
Sign up to set email alerts
|

RCL1 copy number variants are associated with a range of neuropsychiatric phenotypes

Abstract: Mendelian and early-onset severe psychiatric phenotypes often involve genetic variants having a large effect, offering opportunities for genetic discoveries and early therapeutic interventions. Here, the index case is an 18-year-old boy, who at 14 years of age had a decline in cognitive functioning over the course of a year and subsequently presented with catatonia, auditory and visual hallucinations, paranoia, aggression, mood dysregulation, and disorganized thoughts. Exome sequencing revealed a stop-gain mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…And its deficiency may upregulate the expression of genes responsible for ribosome biogenesis. Meanwhile, we also found that Rcl1 protein was distributed in both nucleus and cytoplasm of HCC cell and hepatocyte lines by immunofluorescence, which is consistent with a recent study [31]. Notably, the cytoplasmic Rcl1 protein level of HCC cell lines was dramatically reduced compared to hepatocyte cell.…”
Section: Discussionsupporting
confidence: 91%
“…And its deficiency may upregulate the expression of genes responsible for ribosome biogenesis. Meanwhile, we also found that Rcl1 protein was distributed in both nucleus and cytoplasm of HCC cell and hepatocyte lines by immunofluorescence, which is consistent with a recent study [31]. Notably, the cytoplasmic Rcl1 protein level of HCC cell lines was dramatically reduced compared to hepatocyte cell.…”
Section: Discussionsupporting
confidence: 91%
“…20 Disruptions in SEZ6L cause neurodevelopmental, psychiatric, and neurodegenerative conditions, as well as having a role in motor function. 20, 55, 56 Copy number variation in RCL1 , has also been associated with severe psychiatric disease, 57 and depression. 58 Progressive synaptic loss, or synaptopathy, is a hallmark of MS pathology; 59, 60 evident in both acutely active demyelinating lesions, 61 as well as chronic inactive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Both RCL1 haploinsufficiency and bi‐allelic variants in CAPN1 have been associated with a variety of psychiatric symptoms 5,6,19 . SPG76 shows a wide phenotypic spectrum with pure and complex forms and significant inter‐ and intra‐familial variability 4,6,20–23 .…”
Section: Discussionmentioning
confidence: 99%